Peran Pola Asuh Orang Tua Terhadap Karakter Siswa SDN 01 Kemala Raja - Putri, Kurnia Dwi; Askaf, M.Ardhian Rahali (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Parenting style is the best way for parents to educate their children as an embodiment of their sense of responsibility towards their children. Islam also views the family as the first environment for an individual where he interacts or acquires the basic elements and characteristics of personality. Parents are obliged to create appropriate parenting patterns in educating their children in the family environment. This type of research is qualitative research, namely